Case Report: Immune checkpoint-inhibitor related myotoxicity monitoring using a comprehensive cardiothoracic MRI approach: insights from a clinical case - Boussouar, Samia; Charpentier, Etienne; Abbar, Baptiste; Gonzalez, Jesus; Similowski, Thomas; Kerneis, Mathieu; Allenbach, Yves; Bretagne, Marie; Salem, Joe Elie; Redheuil, Alban (Frontiers in Cardiovascular Medicine, 2025)
Recent advances in immunotherapy have significantly improved outcomes for cancer patients. However, therapies such as immune checkpoint inhibitors (ICIs) can lead to immune-related adverse events, including potentially fatal ICI-myocarditis. The diagnosis of ICI-myocarditis is complex, and cardiac MRI plays a crucial role in identifying this condition. This report presents a novel finding of elevated muscular T1 and T2 relaxation parameters using standard CMR sequences, correlating with the clinical progression of ICI-myotoxicity affecting not only the heart but also the skeletal thoracic muscles and the diaphragm. Identifying diaphragm involvement in these patients is particularly important, as it may result in respiratory failure. MRI has shown significant potential in assessing diaphragmatic function, as well as detecting tissue damage and edema, while also monitoring their evolution over time. This comprehensive, imaging-based approach could guide treatment decisions, including the use of corticosteroids and immunosuppressive therapies. Combining functional and non-invasive tissue assessments in a single MRI examination may enhance early diagnosis and improve the management of patients undergoing ICI therapy.